2013
DOI: 10.1371/journal.pone.0060164
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic and Angiogenic Candidate Genes Predict the Development of Secondary Lymphedema following Breast Cancer Surgery

Abstract: The purposes of this study were to evaluate for differences in phenotypic and genotypic characteristics in women who did and did not develop lymphedema (LE) following breast cancer treatment. Breast cancer patients completed a number of self-report questionnaires. LE was evaluated using bioimpedance spectroscopy. Genotyping was done using a custom genotyping array. No differences were found between patients with (n = 155) and without LE (n = 387) for the majority of the demographic and clinical characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
88
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 65 publications
1
88
0
Order By: Relevance
“…Most of the studies concluded that augmented levels of VCAM-1 are associated with advanced oncogenesis, as for instance in stage 4 breast cancer patients [19,21]. Furthermore, the development of lymphedema after breast cancer surgery also correlated with VCAM expression and VCAM was markedly increased after a dose-dense regimen of chemotherapy [21]. Similar findings could be obtained in colorectal cancer patients, where VCAM was revealed as a biomarker for overall survival and post-operative recurrence [20].…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Most of the studies concluded that augmented levels of VCAM-1 are associated with advanced oncogenesis, as for instance in stage 4 breast cancer patients [19,21]. Furthermore, the development of lymphedema after breast cancer surgery also correlated with VCAM expression and VCAM was markedly increased after a dose-dense regimen of chemotherapy [21]. Similar findings could be obtained in colorectal cancer patients, where VCAM was revealed as a biomarker for overall survival and post-operative recurrence [20].…”
Section: Discussionmentioning
confidence: 74%
“…Recently conducted studies revealed the importance of adhesion process in tumor biology [17]. The existence of adhesion molecules in circulation has been shown in head and neck carcinomas [15][16][17][18][19][20][21]. One of the most important adhesion molecules is the vascular cell adhesion molecule.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations